POLA KEMITRAAN PEMERINTAH KOTA PEKANBARU DENGAN PEKERJA SOSIAL MASYARAKAT DI KECAMATAN TENAYAN RAYA KOTA PEKANBARU TAHUN 2014-2015 - Dwi Sudaryanto; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Among 12 (twelve) sub-districts in the City of Pekanbaru, Tenayan Sub-Feast that most of the inhabitants of poor category. The aim of the research to know the City of Pekanbaru Government partnership with the Community Social workers in the sub-district Tenayan Feast of the City of Pekanbaru years 2014-2015 and to know the obstacles in Pekanbaru City Government partnership with the Community Social workers in the sub-district Tenayan Feast of the City of Pekanbaru Year 2014-2015. Data analysis methods used in this research is a qualitative descriptive analysis method that is attempting to expose the based on the existing phenomena and browse all the facts related to the issues discussed based on the results of research that is the partnership of the Government the City of Pekanbaru With Community Social workers in the sub-district Tenayan Feast of the City of Pekanbaru Year 2014-2015. Based on explanation on the discussion of the City Government Partnership with the Community Social workers in the sub-district Tenayan Feast of the City of Pekanbaru year 2014-2015, it can be concluded the partnership with City Government Community Social workers in the sub-district Tenayan Feast of the City of Pekanbaru Years shaped 2014-2015 mutualistik partnership which is the alliance of two or more parties are equally aware of the aspects of the importance of the partnership for mutual benefit and benefit more so that will be able to achieve optimal. Key Words : The Partnership Pola,